Canalis sinuosus frequency evaluated in cone beam computed tomography in a radiology center, Lima 2021 - Castillo Galindo, Jimmy Luis (2022)
Objective: The objective of this research study was to obtain the frequency of the canalis sinuosus evaluated in cone beam computed tomography in a Lima 2021 radiological center. Materials and Methods: The type of study was basic, non-experimental, cross-sectional and retrospective. 235 tomographic plates between the ages of 18 to 59 years were evaluated. A data collection form was used, which had 6 items, where the frequency of the canalis sinuosus evaluated in Cone-Beam Computed Tomography. Results: Was determined It was found that 33.6% had canalis sinuosus, according to sex 36.2% was more frequent in women, according to the age group the highest frequency of canal sinuosus was between 20 to 59 years, according to the path of the dental piece the highest channel sinuosus frequency was 27.2 % where it was present in the piece 2,2 ; according to the side found, 51.1% was on the right side, and according to the location, 58.2% were bilateral. Conclusions: It was concluded that the frequency of the canalis sinuosus has little presence in the cases evaluated.